Literature as Self-Scrutiny: An Examination of Franz Kafka's "A Hunger Artist" - Gaasland, Rolf (Nordlit, 2023)
The point of departure for this article is Peter U. Beicken's description of Franz Kafka's distinctive narrative rhetoric. It examines the extent to which Beicken's description can be applied to Kafka's short text "A Hunger Artist". The article argues that Beicken's description is relevant to the understanding of this text, but that this particular text also deviates from his description in interesting ways, and in ways that have consequences for how we understand the text's main concern. A conclusion is that the distinctive narrative rhetoric of "A Hunger artist" can be seen in light of an interest that was central to Kafka's life and work, namely the connection between literature and self-scrutiny.